Recognition by a pension body of an event as an accident at work in a case pending before a common court - Ziółkowska, Karolina (Studia Iuridica Toruniensia, 2017)
The aim of this article is to present the issue of accidents at work, but essence is different from previous publications on this subject. Usually taking the problem of accidents at work, the whole subject is focused on the enactment deBnition and individual premises. The definition, which is quite different from the ordinary meaning in Polish, causes many problems in practice. That deBnition has been examined many times by the Supreme Court. Also a lot of problems in the practice of the Social Insurance makes judicial proceedings, related to social security, in particular a question of pension body’s relevance. Therefore, his rights and obligations also do not arise from provisions of the Code of the Administrative Procedure, but from provisions of the Code of Civil Procedure and laws of Social Insurance system. Unfortunately, the proceedings in fact differs from imposed by the legislature.